PENGARUH MOTIVASI INTRINSIK TERHADAP PERFORMA ATLET TAEKWONDO PADA SAAT LATIHAN REVIEW LITERATUERE - Michael Johannes Hadiwijaya Louk; Al Ihzan Tajuddin; Eduardus Mario De Yesus (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2021)
Taekwondo is a type of martial arts sport that is often competed at national or international events. The purpose of this study was "to determine the effect of intrinsic motivation on the performance of taekwondo athletes during training". The type of research used is Literature Review, this research is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing research works and ideas that have been produced by researchers and practically. Based on the results of a review that has been carried out using the Review Journal method, "The Effect of Intrinsic Motivation on the Performance of Taekwondo Athletes During Exercise", the conclusion of this study is that intrinsic motivation has a positive influence on the performance of taekwondo athletes during training, the greater the motivation possessed by athletes, of course. will get better at practice.